2008
DOI: 10.1016/s1472-6483(10)60311-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein kinase A and C inhibitors on follicular inhibin and activin during ovulation

Abstract: Ovulation is associated with a rise in activin A and a decline in pro-alpha C, inhibin A and inhibin B secretion. It is believed that the actions of inhibin and activin during human chorionic gonadotrophin (HCG) stimulation are mediated by protein kinase A (PKA) and/or protein kinase C (PKC). Using an in-vitro murine prenatal follicle culture model, the effects of a PKA inhibitor, Rp-cAMP, and a PKC inhibitor, PKIM, on inhibin and activin gene expression, secretion, ovulation and oocyte maturation were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…On the other side, oocytes express ActRI and ActRII, suggesting their ability to respond to activin (51,110,155,188,328,392). In mouse preantral follicles matured in vitro, the meiotic resumption of the oocyte is associated with increased activin A secretion by the follicle (179). More importantly, exposure to activin A during in vitro maturation stimulates premeiotic oocytes to undergo germinal vesicle breakdown and reach the metaphase II in murine (371,494) as well as in primate species, including the human (5,6).…”
Section: Ovarymentioning
confidence: 99%
“…On the other side, oocytes express ActRI and ActRII, suggesting their ability to respond to activin (51,110,155,188,328,392). In mouse preantral follicles matured in vitro, the meiotic resumption of the oocyte is associated with increased activin A secretion by the follicle (179). More importantly, exposure to activin A during in vitro maturation stimulates premeiotic oocytes to undergo germinal vesicle breakdown and reach the metaphase II in murine (371,494) as well as in primate species, including the human (5,6).…”
Section: Ovarymentioning
confidence: 99%
“…It has been found that both INHβA and INHβB inhibit FSH secretion. The role of these inhibins in the regulation of feedback loops between the pituitary and ovary, as well as their influence on folliculogenesis, has been shown previously (Hua et al ., 2008 ; Myers et al ., 2009 ; Poon et al ., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Activin A stimulates the expression of estrogen receptors in mice [ 84 ]. Finally, in mice, the oocyte resumption of meiosis occurred concomitantly with an increase in activin A [ 85 ].…”
Section: From the Secondary Follicle To The Antral Folliclementioning
confidence: 99%